A novel ultrasonic velocity sensing approach to monitoring state of charge of vanadium redox flow battery. (15th November 2016) - Chou, Yi-Sin; Hsu, Ning-Yih; Jeng, King-Tsai; Chen, Kuan-Hsiang; Yen, Shi-Chern
Highlights: This is the first to apply ultrasonic sensing technique to monitor SOC of VRB. Ultrasound velocity is affected by concentration and temperature of a solution. The ultrasonic sensing is applicable to both positive and negative sides of VRB. An empirical model equation fits the results of this two-component system well. The SOC of a VRB can be properly measured using ultrasonic sensing. Abstract: A novel ultrasonic velocity sensing approach is proposed and investigated to monitor the state of charge (SOC) of a vanadium redox flow battery (VRB, or VRFB). The positive electrode is designated as the energy storage capacity-limiting one so that the molar ratio of the V 5+ ion in the positive electrolyte solution determines the SOC of a VRB. The tested single-cell VRB is connected to an ultrasonic sensor and charged/discharged almost to its two extremes at a constant current of 2 A under various operating temperatures. It is found that the ultrasound velocity exhibits distinct variations in accordance with changes of vanadium ion compositions in the positive electrolyte solution as the SOC of the VRB varies. The SOC obtained can be depicted in a 3D plot in terms of ultrasound velocity and operating temperature. An empirical model equation is proposed and found to fit the experimental results of both charging and discharging stages quite well. The advantages of this SOC sensing approach are that it is totally independent of VRB operations and can be readily applied to both sides of the electrodes. It is expected to develop into a dependable method for accurate and real-time monitoring of SOC for VRB.